New optical hybrid electromotive of B-2-ferromagnetic fiber with some optical applications - Körpınar, Zeliha; Körpınar, Talat (Elsevier Gmbh, 2022)
In this manuscript, we construct new expressions for B-2-optical hybrid magnetic flux density by optical hybrid frame. We derive an expression for the optical hybrid electromotive (f)epsilon phi((T)), (f)epsilon(phi(B1)) and (f)epsilon(phi(B2)) or its conditions. Thus, we get new designs for hybrid ferromagnetic optical demonstrated electromotives for flux linked with poles light coils. We discuss the physical interpretation of our optical results. Hybrid optical magnetic flux surfaces are established in optical hybrid uniform magnetic hybrid surface with fractional numerical new optical results. Finally, we obtain some optical solutions by optical applications.
Keywords: Optical hybrid frame; Optical hybrid electromotive; Optical hybrid flux density; Ferromagnetic model; Berry Topological Phase; Geometric Phase; Polarization; Rotation; Curves; Field